Novel mouse model for Gardner syndrome generated by a large‐scale N‐ethyl‐N‐nitrosourea mutagenesis program. Issue 7 (18th May 2013) - Toki, Hideaki; Inoue, Maki; Motegi, Hiromi; Minowa, Osamu; Kanda, Hiroaki; Yamamoto, Noriko; Ikeda, Ami; Karashima, Yuko; Matsui, Junko; Kaneda, Hideki; Miura, Ikuo; Suzuki, Tomohiro; et al.
Abstract : Mutant mouse models are indispensable tools for clarifying the functions of genes and elucidating the underlying pathogenic mechanisms of human diseases. We carried out large‐scale mutagenesis using the chemical mutagen N ‐ethyl‐ N ‐nitrosourea. One specific aim of our mutagenesis project was to generate novel cancer models. We screened 7012 animals for dominant traits using a necropsy test and thereby established 17 mutant lines predisposed to cancer. Here, we report on a novel cancer model line that developed osteoma, trichogenic tumor, and breast cancer. Using fine mapping and genomic sequencing, we identified a point mutation in the adenomatous polyposis coli ( Apc ) gene. The Apc 1576 mutants bear a nonsense mutation at codon 1576 in the Apc gene. Although most Apc mutant mice established thus far have multifocal intestinal tumors, mice that are heterozygous for the Apc 1576 mutation do not develop intestinal tumors; instead, they develop multifocal breast cancers and trichogenic tumors. Notably, the osteomas that develop in the Apc 1576 mutant mice recapitulate the lesion observed in Gardner syndrome, a clinical variant of familial adenomatous polyposis. Our Apc 1576 mutant mice will be valuable not only for understanding the function of the Apc gene in detail but also as models of human Gardner syndrome.